A simple method of reconstructing a point-like scatterer according to time-dependent acoustic wave propagation. Issue 12 (2nd December 2021) - Chen, Bo; Sun, Yao
Abstract : This paper investigates the approximate solutions to the time-dependent acoustic scattering problem with a point-like scatterer under some basic assumptions and provides a simple method to reconstruct the location of the scatterer. The approximations of the solution to the forward scattering problem are analysed utilizing Green's function and the retarded single-layer potential. Then, based on the approximate solutions, a sampling method is proposed to solve the inverse scattering problem for the location of the scatterer. The proposed method is easy to implement since no equations or matrices have to be computed for the reconstruction. Numerical experiments are provided to show the effectiveness of the method.